2017
DOI: 10.3390/s17061255
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Gold Films Prepared by a Combination of Sputtering and Dealloying for Trace Detection of Benzo[a]pyrene Based on Surface Plasmon Resonance Spectroscopy

Abstract: A wavelength-interrogated surface plasmon resonance (SPR) sensor based on a nanoporous gold (NPG) film has been fabricated for the sensitive detection of trace quantities of benzo[a]pyrene (BaP) in water. The large-area uniform NPG film was prepared by a two-step process that includes sputtering deposition of a 60-nm-thick AuAg alloy film on a glass substrate and chemical dealloying of the alloy film in nitric acid. For SPR sensor applications, the NPG film plays the dual roles of analyte enrichment and suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…SPR-based sensors have been successfully applied in the detection of some volatile compounds and gases like benzene, ammonia, chloroform, ethanol, methanol, ethyl benzene, 2-propanol, toluene, and acetone vapours [8,[26][27][28][29][30][31][32]. The performance of the sensors has been improved through various design modifications which include the incorporation of nanoparticles of different morphologies [33][34][35], bimetallic layers [2,[36][37][38][39], porous gold [40][41][42][43], graphene layer on gold [5,44], conducting and insulating polymer coatings [26,45,46], and metal oxide coatings [47,48]. However, SPR detection of acetone vapour has not been optimized for suitable applicability in diabetes monitoring and screening [32].…”
Section: Introductionmentioning
confidence: 99%
“…SPR-based sensors have been successfully applied in the detection of some volatile compounds and gases like benzene, ammonia, chloroform, ethanol, methanol, ethyl benzene, 2-propanol, toluene, and acetone vapours [8,[26][27][28][29][30][31][32]. The performance of the sensors has been improved through various design modifications which include the incorporation of nanoparticles of different morphologies [33][34][35], bimetallic layers [2,[36][37][38][39], porous gold [40][41][42][43], graphene layer on gold [5,44], conducting and insulating polymer coatings [26,45,46], and metal oxide coatings [47,48]. However, SPR detection of acetone vapour has not been optimized for suitable applicability in diabetes monitoring and screening [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, this makes the fabrication process of the SPR sensors complicated and exhaustive. To overcome this problem, Wang et al adopted nanoporous gold (NPG) film as an effective and alternative approach for the SPR sensor in the trace detection of BaP [35]. The NPG film could not only dramatically enhance the sensitivity for the great enrichment of BaP throughout the entire thickness but also support the surface plasmon wave with a simple structure of the SPR sensor (Figure 4b).…”
Section: Spr Sensorsmentioning
confidence: 99%
“…The detection limit for BaP was 5 pmol•L −1 , which was increased by 20 times compared to that of conventional SPR sensors ( Figure 5). Therefore, this suggested that the technique in SPR sensors shows enormous potential for trace detection and monitoring of small-molecular environmental pollutants [35].…”
Section: Spr Sensorsmentioning
confidence: 99%
See 2 more Smart Citations